Spiral wound gaskets with fiber Bragg grating sensors. (1st December 2022) - Cloostermans, Ben; Pronk, Dick; Bruckenburg, Björn; Geernaert, Thomas
Abstract: Modern sealing components are used in a wide range of industrial processes. The recent global attention for reducing emission of environmentally harmful substances motivates gasket manufacturers to quantify the performance of sealing gaskets. We investigate the use of fiber Bragg grating sensors for measuring seating stress on a spiral wound gasket. The fiber-optic sensors are integrated in the gasket, following a particular instrumentation strategy. The instrumented gaskets are first installed in a standardized flange following a state-of-the-art installation protocol. Then, the gaskets are unloaded with a particular unloading strategy to simulate sealing performance loss. We compare the load in the mounting bolts during the (un)loading procedure with the response of the FBG sensors in the gasket and find a high correlation. We thus evidence the potential of fiber-optic sensors for measurements during installation as well as monitoring of sealing gaskets serving the accountability of these components.